Selectivity hypothesis and task bind: Explaining gender difference in NPD’s cost information and control adoption - Wardani, Rika Alvira Brisa; Jatiningsih, Dyah Ekaari Sekar (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to examine how gender will differentiate the effect of cost information and management control system adoption during the New Product Development (NPD) process. The importance of such research lies in the suggested development of gender-diverse teams to achieve optimum performance.Design/Methodology/Approach: An experimental design was employed to test proposed hypotheses. Data from 117 Accounting undergraduate students as surrogates of professional NPD designers were analyzed using Analysis of Covariance (ANCOVA).Research findings: Results revealed that female designers, due to comprehensive processing and stereotype threat, achieved more cost-effective designs with specific information and diagnostic control systems. In comparison, males would achieve better performance using relative information and designing in interactive control since they tended to be heuristic and free from stereotyping.Theoretical contribution/Originality: This research confirms gender differences in NPD. The explanation using the selectivity hypothesis and task bind mechanism contributes to the literature by supporting clear causal relationships in gender-related NPD contexts.Practitioner/Policy implication: In NPD, management should consider the proper presentation of information across specific users, including across teams with gender variability. Further, the design of the management control system should consider variability once the gender-diverse team has been developed.Research limitation/Implication: The causal relationship in this study was limited to a specific experimental setting, which did not reflect all complexities in practice. However, the interplay between variables under study leads to the avenue for future research to broaden the test into different metrics of NPD performance, types of information, and possible designer variability.